Haemoglobin E Trait: A Frequently Incriminated Innocent Trait - Biswas, Akhil Ranjon; Ara, Tasneem (Journal of Dhaka Medical College, 2017)
Background: Haemoglobin (Hb) level in Hb E trait or heterozygous Hb E usually does not go bellow reference level, so does not causes any significant anaemia. However, many medical practitioner conclude Hb E trait as a cause of anaemia when they find Hb E trait in the course of evaluation. Objective:The objective of this case series is to find out whether Hb E trait can be a cause of significant anaemia or not. Methods: A series of cases of Hb E trait with significant anaemia was systematically evaluated to find out the real cause of anaemia and treated accordingly and followed up to find out whether Hb E trait itself can be a cause of anaemia at all. Result: Out of 13 anaemic patients presented with the diagnosis of Hb E trait, 1 was not Hb E tarit at all but Hb E/â thalassaemia. Out of 12 actual Hb E trait, 1 expired within treatment for acute lymphoblastic leukaemia. Correctable cause of anaemia was found in 10 out of remaining 11 cases and 1 case had very high CRP and didnt comply with further investigation. Anaemia was corrected with treatment in 9 cases and partially corrected in 1 case who was not compliant to regular treatment. Conclusion: Hb E trait is not a cause of significant anaemia and a probable incidental finding in anaemic patient undergoing Hb electrophoresis, especially in areas where Hb E is quite common like Bangladesh. J Dhaka Medical College, Vol. 26, No.1, April, 2017, Page 32-35